2020
DOI: 10.1002/er.6229
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior of lithium‐ion battery in microgrid application: Impact and management system

Abstract: Summary Safe and reliable operation is among the considerations when integrating lithium‐ion batteries as the energy storage system in microgrids. A lithium‐ion battery is very sensitive to temperature in which it is one of the critical factors affecting the performance and limiting the practical application of the battery. Furthermore, the adverse effects differ according to the temperature. The susceptibility of lithium‐ion battery to temperature imposes the need to deploy an efficient battery thermal manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 119 publications
(304 reference statements)
0
6
0
Order By: Relevance
“…B, Hybrid BTMS component parts individually. 54 BTMS, battery thermal management system. energy use and save the environment.…”
Section: Working Principle Of a Tegmentioning
confidence: 99%
See 2 more Smart Citations
“…B, Hybrid BTMS component parts individually. 54 BTMS, battery thermal management system. energy use and save the environment.…”
Section: Working Principle Of a Tegmentioning
confidence: 99%
“…The TEC limits' cooling capabilities are previously mentioned. Zhang et al 54 suggested a hybrid BTMS for prismatic Li‐ion battery cell to combine TEC and HP, where the HP is employed to dissipate the heat on the hot side of the TEC. The aluminum sheet and HP were attached to the TEC hot and cold sides, as indicated in Figure 7B.…”
Section: Thermoelectric Coolermentioning
confidence: 99%
See 1 more Smart Citation
“…Lithium-ion batteries (LIBs) are used in various devices due to their high energy density. [1][2][3] However, the scarcity and price of lithium resources force us to find alternative new energy sources. Meanwhile, combustible organic electrolytes cannot achieve safety under foldable conduction.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium‐ion batteries (LIBs) are used in various devices due to their high energy density 1‐3 . However, the scarcity and price of lithium resources force us to find alternative new energy sources.…”
Section: Introductionmentioning
confidence: 99%